1984
DOI: 10.1117/12.945111
|View full text |Cite
|
Sign up to set email alerts
|

Practical Coherent Otdr At 1.3 μm

Abstract: The performance of a coherent OTDR system operating at 1.3 µm is described. Two sources have been used -a Nd:YAG laser and a semiconductor laser with increased coherence. With the latter source, greater than 24 dB one way range has been achieved with accurate determination of fault magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is an ideal behavior for a backscatter source, since it ensures a degree of fading, which, after averaging, causes the speckle-like appearance of the backscatter trace to be smoothed out. Using this source, Wright et al [46] demonstrated a heterodyne OTDR with a one-way range of approximately 24 dB. The system operating parameters were PL = -15 dBm, W = 2 ps.…”
mentioning
confidence: 99%
“…This is an ideal behavior for a backscatter source, since it ensures a degree of fading, which, after averaging, causes the speckle-like appearance of the backscatter trace to be smoothed out. Using this source, Wright et al [46] demonstrated a heterodyne OTDR with a one-way range of approximately 24 dB. The system operating parameters were PL = -15 dBm, W = 2 ps.…”
mentioning
confidence: 99%
“…6. Heterodyne Detection: In the heterodyne detection method [30]- [32], signal light and local oscillator light are mixed in the photodetector, and the beat signal is detected ( Fig. 9) [31].…”
Section: Photon Counting Detectionmentioning
confidence: 99%